(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we wanted to investigate the oxidative stress level and some antioxidant parameters in angiography workers exposed to high dose x-ray. Material and Methods: The study included 47 angiography workers and 50 healthy control group. Some antioxidant parameters (superoxide dismutase, catalase, and reduced glutathione) and levels of malondialdehyde, which is a marker of oxidative stress, were measured in the blood samples of all participants.Results: There was a significant increase in oxidative stress marker MDA levels and a significant decrease in antioxidant enzyme (superoxide dismutase, catalase and reduced glutathione) levels in all individuals of the study group compared to the control group (p0.001 for all). Conclusion: Our results indicated that oxidative stress level increased and some antioxidant enzyme levels (superoxide dismutase, catalase and decreased glutathione) decreased in angiography workers exposed to long-term high-dose ionized radiation. We have linked this to the oxidant-antioxidant balance disorder caused by increased free radicals due to ionizing radiation, as noted in the literature.